Water management for Schinus terebinthifolius Raddi seedlings in degradable containers - Viégas, Lucas Bertacini [UNESP]; Simões, Danilo [UNESP]; de Lima, Kaio Baron [UNESP]; da Silva, Magali Ribeiro [UNESP] (FapUNIFESP (SciELO), 2018)
The research consisted of two experiments (64 and 85-day production cycles), applying three irrigation depths (8, 11 and 14 mm) to determine the most appropriate depth, using Ellepot™ degradable containers for the production of Schinus terebinthifolius seedlings; the possibility of shortening the production cycle; and the influence of water management in nursery on the early development of plants in pots. Results indicated that the most appropriate irrigation depth is 14 mm for both the 64 and 85-day production cycles; that it is possible to produce Schinus terebinthifolius seedlings with a shortened cycle, given that quality indicators were adequate; and that there was an influence of water management used in the nursery on the development of plants in pots for 64-day seedlings.
Keywords: Brazilian pepper tree; Container development; Ellepot™; Forest nursery; Irrigation depth